The Search for a Common Language: Environmental Writing and Education - Crumbly, Paul (Utah State University, University Libraries, 2005)
A stellar group of writers, scientists, and educators illuminate the intersections between environmental science, creative writing, and education, considering ways to strengthen communication between differing fields with common interests.